Total Syntheses of Eudistomins Y1–Y7 by an Efficient One‐Pot Process of Tandem Benzylic Oxidation and Aromatization of 1‐Benzyl‐3, 4‐dihydro‐β‐Carbolines. Issue 16 (5th April 2013) - Trieu, Tien Ha; Dong, Jing; Zhang, Qiang; Zheng, Bo; Meng, Tian‐Zhuo; Lu, Xia; Shi, Xiao‐Xin
Abstract: The first total synthesis of eudistomin Y7 (7 ) and total syntheses of eudistomins Y1 –Y6 (1 –6 ) are described. An efficient room‐temperature conversion of 1‐benzyl‐3, 4‐dihydro‐β‐carbolines (11 ) into 1‐benzoyl‐β‐carbolines (14 ) by a one‐pot process of tandem benzylic oxidation and aromatization as the key step of these total syntheses was also studied in detail. Abstract : The first total synthesis of eudistomin Y7 (7 ) and total syntheses of eudistomins Y1 –Y6 (1 –6 ) are described. An efficient room‐temperature conversion of 1‐benzyl‐3, 4‐dihydro‐β‐carbolines (11 ) into 1‐benzoyl‐β‐carbolines (14 ) by a one‐pot process of tandem benzylic oxidation and aromatization as the key step of these total syntheses was also studied in detail.